Pengaruh motivasi belajar terhadap self-regulated learning pada mahasiswa - Rinda Fenty Prastiwi (Universitas Negeri Padang, 2021)
The purpose of this study was to determine the significant effect of learning motivation on self-regulated learning in students of the guidance and counceling study program batch 2018 faculty of teacher training and science Satya Wacana Christian University, Salatiga. This study used a sample of 57 students. The method used was a questionnaire. The data analysis technique used in this study was simple linear regression with the help of the SPSS version 20.0 program. The simple linear test results show that learning motivation has no effect on self-regulated learning in students of the Guidance and Counseling Study Progrm batch 2018 FKIP Satya Wacana Christian Univesity, Salatiga. This can be seen from the results of the simple linear regression test on the Model Summary, it can be seen that the value of the Adjusted R square is 0.006 which means that it is 0.6%. The F count value is 0.312, P 0,579 >0.05, so it can be concluded that there is no effect of Learning Motivation on Self-regulated in students of the guidance and counceling study program batch 2018 faculty of teacher training and science Satya Wacana Christian University, Salatiga.